Empon Empon Herbal Intake and Increased Breast Milk Production: Konsumsi Jamu Empon-Empon dan Peningkatan Produksi ASI Postpartum - Sari, Pramudya Novita; Astuti, Dwi; Indrianingrum, Irawati (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Breast milk production during the postpartum period is a critical factor in successful breastfeeding, yet many mothers experience challenges in achieving adequate lactation. Specific Background: Traditional herbal practices such as empon-empon consumption are widely used in Indonesian communities as part of postpartum care, believed to support lactation through bioactive compounds. Knowledge Gap: Previous studies have primarily examined general herbal benefits, with limited contextual evidence on the relationship between empon-empon consumption and breast milk production within independent midwifery practices. Aims: This study aims to analyze changes in breast milk production before and after consuming empon-empon herbal drink among postpartum mothers at PMB Dwi Ningrum, Demak. Results: Using a quasi-experimental one-group pretest–posttest design involving 79 respondents, findings showed an increase in the proportion of mothers with smooth breast milk production from 24.1% before intervention to 60.8% after consumption, with statistically significant differences based on the Wilcoxon test. Novelty: This study provides empirical, context-specific evidence integrating local cultural practices and lactation outcomes within community-based midwifery services. Implications: The findings suggest that empon-empon herbal consumption can be considered as a complementary approach to support lactation, while emphasizing the importance of comprehensive breastfeeding management, including maternal nutrition, psychological condition, and family support. Highlights • Breast milk flow increased substantially after herbal consumption period• Significant statistical difference observed between pretest and posttest conditions• Community-based traditional practices documented within midwifery service context Keywords Postpartum Period; Empon-Empon Herbal Drink; Breast Milk Production; Postpartum Mothers; Pretest Posttest Design